Long-term in vivo gene expression in mouse kidney using φC31 integrase and electroporation. (12th February 2015) - Otani, Yuki; Kawakami, Shigeru; Mukai, Hidefumi; Fuchigami, Yuki; Yamashita, Fumiyoshi; Hashida, Mitsuru
Abstract: Background : Achieving long-term gene expression in kidney will be beneficial for gene therapy of renal and congenital diseases, genetic studies constructing animal disease models, and the functional analysis of disease-related genes. Purpose : The purpose of this study was to develop an in vivo long-term gene expression system in murine kidney using φC31 integrase. Methods : Gene expression in cultured RENCA, TCMK-1, and HEK293 cells was assessed. The long-term in vivo gene expression system in the kidney was achieved by co-transfecting 5 µg of pORF-luc/attB as a donor plasmid and 20 µg of pCMV-luc as a helper plasmid into the right kidney of mice by electroporation. Luciferase expression levels were measured to determine longevity of the expression. Results : Significantly high luciferase expression levels were observed in cultured RENCA, TCMK-1, and HEK293 cells over 1 month compared with controls (non-integrase system). The luciferase cDNA sequence was integrated at a pseudo attP site termed mpsL1. In vivo luciferase expression levels in the integrase group were sustained and significantly higher than those in the control group over 2 months. Furthermore, φC31 integrase-transfected cells had less genomic DNA damage caused by integrase expression. Discussion and conclusion : These results demonstrated that the φC31 integrase system could produce long-term (2 months) in vivo gene expression in mouse kidney.